2016
DOI: 10.1177/0044118x16680546
|View full text |Cite
|
Sign up to set email alerts
|

Natural Mentors, Racial Pride, and Academic Engagement Among Black Adolescents

Abstract: The current study examined the potential of relational closeness in the natural mentoring relationships (NMRs) of Black students to counter and protect against the noxious effects of school-based discrimination on academic engagement. The study sample included 663 Black students between the ages of 12 and 19 ( M = 14.96 years, SD = 1.81 years), all reporting a natural mentor. Approximately half of participants were female (53%). Participants were recruited from three different school districts in a Midwestern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 53 publications
5
27
1
Order By: Relevance
“…Although natural mentors who were affiliated with the institution were slightly better positioned to support students, those outside of the PWI also played a role in the coping process. Consistent with previous research, the natural mentors with whom students discussed race-related stressors were also Black (Wittrup et al, 2016), and many students commented on the importance of a shared experience when identifying individuals who could provide support in the context of race-related stressors. Black students felt that individuals who did not possess a shared understanding of race-related stressors, particularly those that may be unique to the PWI setting, would not be able to provide the support students needed.…”
Section: Discussionsupporting
confidence: 70%
“…Although natural mentors who were affiliated with the institution were slightly better positioned to support students, those outside of the PWI also played a role in the coping process. Consistent with previous research, the natural mentors with whom students discussed race-related stressors were also Black (Wittrup et al, 2016), and many students commented on the importance of a shared experience when identifying individuals who could provide support in the context of race-related stressors. Black students felt that individuals who did not possess a shared understanding of race-related stressors, particularly those that may be unique to the PWI setting, would not be able to provide the support students needed.…”
Section: Discussionsupporting
confidence: 70%
“…The perceived availability of social support reduced some symptoms of stress associated with the migration process and made the youths more resilient, despite enduring significant adversity. The impact of mentoring on the promotion of resilience in adolescents from ethnic minorities supports the findings of a recent literature review [ 36 , 60 , 61 , 62 ].…”
Section: Discussionsupporting
confidence: 81%
“…The quality of mentorship may shape resilience among African American youth (e.g., mentorship warmth, type of support), so future research examining the interaction of ORI and natural mentorship would benefit by assessing mentorship quality (see Albright, Hurd, & Hussain, ; Hurd & Zimmerman, ). For example, mentorship quality and the nature of support provided have been shown to augment the protective effect of natural mentoring relationships (Hurd, Albright, Wittrup, Negrete, & Billingsley, ; Hurd & Sellers, ; Wittrup et al., ). Third, although our study identified that high levels of ORI paired with natural mentorship was protective, religious socialization for some African American girls may shape the protectiveness of religious involvement (Bowie, Juon, Taggart, Thorpe, & Ensminger, ; Butler‐Barnes et al., ; Gutierrez, Goodwin, Kirkinis, & Mattis, ; Hope et al., Taggart et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research points to the potential of natural mentors to help vulnerable adolescents display positive adaptation in the face of risk. Specifically, natural mentoring relationships have been linked to improved psychological well‐being, more positive connections with peers and parents, academic success, and fewer problem behaviors among marginalized youth (DuBois & Silverthorn, ; Griffith, Hurd, & Hussain, ; Hurd, Sánchez, Zimmerman, & Caldwell, ; Hurd, Varner, & Rowley, ; Hurd & Zimmerman, ; Klaw, Rhodes, & Fitzgerald, ; Kogan, Brody, & Chen, ; Sánchez, Esparza, & Colón, ; Wittrup et al., ). Scholars have suggested that natural mentoring relationships are a long‐standing tradition in the African American community (Billingsley & Billingsley, ; Stack, ; Stewart, ).…”
Section: Introductionmentioning
confidence: 99%